Un problema de optimización convexa y su aplicación - Blas Baltodano, Luis Alberto (2015)
In this paper we identify techniques that studies the convex optimization and its importance_x000D_ in engineering applications, telecommunications, signal processing, economics,_x000D_ etc. then identifies the structure of the optimal solution, because any local solution is_x000D_ also a global solution and also there is associated duality theory of convex optimization_x000D_ problem and optimal conditions point that show whether the exact solution is found or_x000D_ best approximation to it._x000D_ In recent years there have been significant advances in the use of convex optimization_x000D_ techniques in various application areas, such as those mentioned in the preceding_x000D_ paragraph and problems such as: location of sensors; Power optimization in mesh-like_x000D_ networks; image processing, production, etc. especially finding efficient solution to intractable_x000D_ problems that were originally manner._x000D_ Therefore in this paper the mathematical models for solving convex optimization problems_x000D_ and where the optimal solution is found techniques is presented. In this paper the_x000D_ mathematical models for solving convex optimization problems and where the optimal_x000D_ solution is presented techniques._x000D_ Due to the various applications of convex optimization, in this paper we solve the problem_x000D_ of optimizing a convex function f : Rn → R, under restrictions by posing convex_x000D_ regions also main objectives, analysis of the solution of the problem, the characterization_x000D_ of the solution of a convex problem and the application of this theory in economics or_x000D_ engineering problems